PERBANDINGAN AKTIVITAS PENGHAMBATAN ENZIM TIROSINASE OLEH FRAKSI ETIL ASETAT DAUN PATIKALA (Etlingera elatior) DAN HIDROKUINON SECARA In Vitro - Selfyana Austin Tee; Apriyanto Apriyanto; Musdalipah Musdalipah; Elfirah Elfirah (Universitas Islam Negeri Alauddin Makassar, 2020)
Etlingera is one of the genus Zingiberacea which consists of 150 - 200 species in the world, and there are 48 species that grow in Sulawesi and 14 species of which are scattered in Sulawesi. Patikala (Etlingera elatior) has a bioactive compound in the form of flavonoids. Withdrawal of flavonoid compounds in plants is carried out using ethyl acetate solvents. One of the enzymes in the body is the tyrosinase enzyme. The tyrosinase enzyme is the main pathway in the pigmentation process, causing melanin pigment. This study aims to compare the inhibitory activity of the tyrosinase enzyme in the paticala fraction of ethyl acetate (Etlingera elatior) and hydroquinone in vitro. The research method used was a quasi experimental consisting of the treatment group and the control group with measurements made after the treatment was given (posttest only design with non equivalent group). Concentration of ethyl acetate fraction of patikala leaves used were 7.8125 µg / mL, 15,625 µg / mL, 31.25 µg / mL, 62.5 and 125 µg / mL with positive control of hydroquinone, respectively. Based on the results obtained, Inhibitory activity of the tyrosinase enzyme by the paticala leaf ethyl acetate fraction with a concentration of 125 μg. The inhibitory activity of the tyrosinase enzyme by both samples increased with increasing concentration